A teologia política de João Calvino (1509-1564) na Institutas da Religião Cristã (1536) - Mendes, Eber da Cunha (2009)
This research want to analyze the nature of the John Calvin politics theology (1509- 1564) in your work The Institutes of the Christian Religion (1536) especially in the chapter in which he treats of the public administration. Calvino wrote a political theology that legitimated the Protestant cause in Geneva starting from theological arguments and biblical hermeneutics. He thought, he interpreted and built a political theory according to the perspective of the social group of which was member, looking for to establish new organization manners, social relationships and of being able to, intended for the new Protestant society. In this sense, John Calvino's writings are marked by the reformed Christian apprehensions of his reality. In them, John Calvino presented the way as he interpreted, he thought and built it and he gave to read this power in Geneva. His theology and classifications produced sense, hierarchies, identities and relationships of power. He conceived the world starting from their biblical presuppositions and according to the interests of the Protestantism that were related to the universalization desire and diffusion of the values and of the reformed ethics.The research too analyze the theologies principles, anthropologies, hermeneutics and socials; and by end , explain and reflect on the politics ideas in the politic chapter of the Institutes, for exemple, resistance to tyranny government, shapes of the government and the politics organization.